Evaluación energética del sistema de iluminación de interiores del bloque B de la Universidad Técnica de Cotopaxi, 2013. Diseño de un sistema eficiente de alumbrado para interiores basado en tecnologías LED. - Cevallos Carvajal, Alex Santiago (2013)
We present the results of the energy evaluation inside lighting system at the Technical University of Cotopaxi, Block B 2013. With mercury fluorescent lamps. Measurements of light intensity, luminous flux, calculations and light output uniformity in the different points of light thrown shortfalls resulting visual comfort, low light levels as INEN standards and excessive energy consumption per start unnecessary luminaires. We conducted a feasibility analysis for replacing the current lighting system with a more efficient interior. The cost analysis reveals economic losses for an excessive energy consumption and decrease the useful life of traditional luminaires. We propose the design of a more efficient system for inside lighting based on LEDS technology based T8 fluorescent tubes of 58 W and 13 W easy to install, it does not require maintenance, with an intelligent control that minimizes on-off times use unnecessary high luminous flux and uniformity, visual comfort and effectiveness indoor lighting energy savings of 70- 80% in comparison with the current system.